Probing the furanose conformation in the 2 `-5 ` strand of isoDNA:RNA duplexes by freezing the nucleoside conformations - Erande, Namrata D.; Gunjal, Anita D.; Fernandes, Moneesha; Kumar, Vaijayanti A. (Chemical Communications, 2011)
Sugar conformations in the isoDNA strand of isoDNA : RNA duplexes are preferred S-type locked/frozen in contrast to N-type locked conformations preferred in DNA: RNA duplexes.

Phyto-inspired cyclic peptides derived from plant Pin-II type protease inhibitor reactive center loops for crop protection from insect pests - Sailthedkar, Nidhi S.; Joshi, Rakesh S.; Yadav, Amit K.; Seal, Shubhendu; Fernandes, Moneesha; Giri, Ashok P. (Biochimica ET Biophysica Acta-General Subjects, 2019)
Background: Natural defence of plants against insect pests involves protease inhibitors (PIs) that interfere with insect digestive proteases. Pin-II type plant PIs are wound inducible upon insect damage and possess multiple inhibitory repeat domains that can inhibit trypsin and chymotrypsin-like proteases in the insect midgut. Yet, their agricultural ex-vivo application is limited due to large molecular size and environmental instability, which could be overcome by small peptides. Methods: Bicyclic peptides were designed by grafting Pin-II PIs derived reactive center loop (RCL) on synthetic tris(bromomethyl)benzene scaffold. In vitro binding with trypsin-like proteases was evaluated by biochemical and biophysical assays, followed by molecular dynamics simulations. In vivo effects on two major lepidopteran insect pests, Helicoverpa armigera and Spodoptera litura were studied upon feeding with peptide treated leaves. Affinity based pull down assays were used to identify target proteins in insect gut. Results: Bicyclic RCLs showed ten-fold enhanced protease inhibition compared to their linear counterparts. They exhibited feeding deterrence and growth reduction of lepidopteran insects. Bicyclic peptides predominantly interact with midgut serine proteases. Possible binding modes involve simultaneous interaction with the active site and specificity-determining residues of insect gut trypsin. Conclusion: Bicyclic peptides are potent inhibitors of serine proteases in the insect midgut. They cause feeding aversion and larval growth retardation. Bi-domain cyclic peptides interact with two sites on trypsin, leading to enhanced efficacy over linear RCL peptides. General significance: Bicyclic peptides mimic natural PIs by inhibiting insect proteases leading to growth reduction, thus, could be used as pest control molecules in agriculture.
Keywords: Cyclic peptide; Lepidoptera; Pest control; protease inhibitor; Reactive loop

p-Nitrophenylcarbonates: a new class of compounds for chemodosimetric colorimetric fluoride anion sensing detectable by the naked eye - Yadav, Amit Kumar; Chilukuri, Harsha; Kumari, Linthoinganbi Raj; Karthikeyan, Muthukumarasamy; Fernandes, Moneesha (ChemistrySelect, 2019)
A new class of compounds containing the p-nitrophenylcarbonate motif is reported, that can selectively sense fluoride anions over other halide anions with a detection limit ranging from 0.29 to 0.48 mu M. The fluoride ion acts as nucleophile, leading to the liberation of p-nitrophenol, that is easily detectable and quantifiable colorimetrically.
Keywords: colorimetric sensing; p-nitrophenyl carbonate; selective fluoride detection

PNA-mediated efflux inhibition as a therapeutic strategy towards overcoming drug resistance in Mycobacterium smegmatis - Ghosh, Saptarshi; Cotta, Karishma Berta; Hande, Aniket A.; Fernandes, Moneesha; Mehra, Sarika (Microbial Pathogenesis, 2021)
The emergence of antibiotic-resistant strains of Mycobacterium tuberculosis and the decelerating development of new and effective antibiotics has impaired the treatment of tuberculosis (TB). Efflux pump inhibitors (EPIs) have the potential to improve the efficacy of existing anti-TB drugs although with toxicity limitations. Peptide nucleic acids (PNAs), oligonucleotide mimics, by virtue of their high nucleic acid binding specificity have the capability to overcome this drawback. We, therefore, investigated the efflux pump inhibitory properties of a PNA designed against an efflux pump of Mycobacterium smegmatis. LfrA, an efflux pump found in M. smegmatis, is majorly involved in conferring innate drug resistance to this strain and, therefore, was selected as a target for gene silencing via PNA. qRT-PCR and EtBr assays confirmed the EPI activity of the anti-lfrA PNA. On testing the effect of the anti-lfrA PNA on the bactericidal activity of a fluoroquinolone, norfloxacin, we observed that 5 mu M of anti-lfrA PNA in combination with norfloxacin led to an enhanced killing of up to 2.5 log-fold against wild-type and a lab-generated multidrug resistant strain, exemplifying its potential in countering resistance. Improved efficacy was also observed against intra-macrophage mycobacteria, where the drug-PNA combination enhanced bacterial clearance by 1.3 log-fold. Further, no toxicity was observed with PNA concentrations up to 4 times higher than the efficacious anti-lfrA PNA concentration. Thus, PNA, as an adjuvant, presents a novel and viable approach to rejuvenate anti-TB therapeutics.
Keywords: Adjuvant; Antibiotic resistance; Antisense; Efflux pump; Gene silencing; Mycobacteria; Peptide nucleic acid (PNA)